Biocatalyst CAL-B catalyzed synthesis of modified nucleosides: An overview. Issue 13 (3rd July 2019) - Kumar, Rajesh; Kumar, Vijay; Mathur, Divya; Kumar, Ram; Kumar, Arbind; Prasad, Ashok K.
Abstract: Nucleosides are valuable biologically active compounds, which display antitumour and antiviral activities. Various types of bioactive nucleosides are designed to improve their therapeutic efficacy, However this strategy faces the difficult selectivity issues of nucleoside chemistry. Therefore, the goal of this review is to give an idea of the opportunities provided by biocatalyst CAL-B procedures in the preparation of different types of bioactive nucleoside compounds. The function of Candida Antarctica lipase-B (CAL-B) in organic synthesis is reviewed. This enzyme has been found to be a principally efficient and robust lipase catalyzing an unexpected variety of reactions including many different regio- chemo, and diastereo-selective synthesis. Moreover, the structure of Candida Antarctica lipase-B is an example of an enzyme for which its specificity has been predicted based on acylation and deacylation mechanism on substrates. Graphical Abstract: